Narrative Literature Review of Potential Atrial Fibrillation Mechanism of Action Induced by Discontinuation of Benzodiazepines - Agnė Okulevičiūtė; Gabija Laubner Sakalauskienė (Acta Medica Lituanica)
Introduction: Benzodiazepines are commonly prescribed but often misused, leading to dependence and withdrawal symptoms. Increased worldwide prescriptions raise adverse effects and overdose concerns, especially for the elderly. Caution is needed in prescribing and considering alternative treatments to minimize risks.